HBV/HDV coinfection: A long-lasting indication for liver transplantation. (March 2023) - Manuli, C.; Calleri, A.; Saracco, M.; Tandoi, F.; Cocchis, D.; Romagnoli, R.; Martini, S.
Abstract : Background: Liver transplantation(LT) remains the only therapeutic option for decompensated HDV-liver disease. We aimed to compare the characteristics of HBV- versus HBV/HDV-positive LT recipients in our high-volume Center in the last 12 years. Methods: All HBsAg+ patients who underwent LT in our Centre from January 2010 to December 2021 were included. Post-LT anti-HBV prophylaxis was performed with anti-HBs immunoglobulins and nucleos(t)idic analogues. Immunosuppression was based on calcineurin inhibitors, mycophenolate, and steroids (tapered to suspension in 6 months). Results: In the study period, 1710 LTs were performed in our Centre. LT indication was HBsAg+ liver disease in 290 patients (17.0%). 147/290 patients (50.7%) were HBV monoinfected, while 143 (49.3%) were HBV/HDV coinfected. Median age was lower in HBV/HDV patients (55.2 years, IQR 49.1-60.2) compared to HBV patients (59.0 years, IQR 55.2-63.1), p<0.001. Female gender was more frequent in HBV/HDV group (28.7% vs. 11.6%, p<0.001). Median MELD was higher in HBV/HDV coinfected LT recipients (15 vs 11, p<0.001). Hepatocellular carcinoma (HCC) was the main LT indication in both groups, with higher prevalence in HBV monoinfected patients (74.1% vs 54.5%, p<0.001). The proportion of foreign-origin patients increased in the HBV/HDV group from 9.7% in 2010-2015 to 42.0% in 2016-2021 one (p<0.001), whereas it remained stable in the monoinfected group (9.9% vs 16.7%, p=0.22) (Table 1 ). Median post-LT follow-up time was 6.9 years (IQR 4.0-9.9). Overall 5-year survival was 92.2%: 95.5% in HBV/HDV and 88.9% in HBV group, p=0.009. All patients remained HBV-DNA negative after LT. Conclusions: Our experience shows that HDV still represents a noteworthy indication for LT, accounting for up to 50% of transplants performed for HBV, with a prevalence of 61.2% in the foreign subgroup. Coinfected patients need LT at a younger age and with higher MELD score compared with the HBV population, but they show an excellent 5-year post-LT survival.